Biological notes on two species of Oxycorynus (Coleoptera: Belidae) associated with parasitic plants of the genus Lophophytum (Balanophoraceae), and new distribution records in Argentina Notas biológicas sobre dos especies de Oxycorynus (Coleoptera: Belidae) asociadas con plantas parásitas del género Lophophytum (Balanophoraceae), y nuevos registros de distribución en Argentina - María S. Ferrer; Adriana E. Marvaldi; Héctor A. Sato; Ana M. Gonzalez (Revista de la Sociedad Entomológica Argentina, 2011)
This contribution provides new information on the association of weevils of the genus Oxycorynus Chevrolat (Belidae: Oxycoryninae) with parasitic plants of the genus Lophophytum Schott & Endl. (Balanophoraceae). New distribution records of Oxycorynus in Argentina are provided. Se brinda nueva información sobre la asociación de gorgojos del género Oxycorynus Chevrolat (Belidae: Oxycoryninae) con plantas parásitas del género Lophophytum Schott & Endl. (Balanophoraceae). Se proveen, además, nuevos registros de distribución de Oxycorynus en Argentina.